Age-related Decline in Renal Function is Attenuated in Master Athletes - Rosa, Thiago dos Santos; Corrêa, Hugo Luca; Barbosa, Lucas Pinheiro; Santos, Patrick Anderson dos; Leite, Patrício Lopes de Araújo; Aguiar, Samuel Silva; Deus, Lysleine Alves; Maciel, Larissa Alves; Neves, Rodrigo Vanerson Passos; Simoes, Herbert Gustavo (International Journal of Sports Medicine, 2021)
This study analyzed the kidney function and biomarkers of health in lifelong-trained sprinters and endurance runners, and compared them to untrained aged-matched and young controls. Sixty-two men (21–66 yr.) were recruited and allocated as master athletes from sprints (n=25), master athletes from endurance events (n=8), untrained middle-aged (n=14) and young controls (n=15). Participants underwent anamnesis, anthropometric measures and blood sampling for biochemical analyses of klotho, FGF23 and estimated glomerular filtration rate. Master sprinters presented better kidney function in relation to endurance athletes and their untrained peers (P<0.0001). A number of biochemical variables were observed that negatively (i. e., GDF-15, TGF-Beta, IL-18) or positively (i. e., klotho/FGF23 ratio and sestrin-2) correlated with eGFR. Sestrin-2 presented the strongest association with eGFR (r=0.5, P=0.03). Results also revealed that lifelong-trained individuals presented the highest probability of having better values for cystatin C and thus an estimated glomerular filtration rate that was 37–49% higher than untrained peers. Master sprinters presented better kidney function in relation to endurance athletes and middle-aged untrained peers. Sestrin-2 may play a role in exercise-induced kidney function protection.
Keywords: klotho; sestrin; FGF-23; inflammation; oxidative stress; runners